Swahili translation of the Vicious Worm health information tool - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
The computer-based health-education tool ‘The Vicious Worm’ was developed to create awareness and provide evidence-based health education as a specific measure in control strategies. To increase the reach of the tool, a new version in Swahili was developed and can now be downloaded for free from http://theviciousworm.sites.ku.dk.